Biodegradation of Poly(R,S)-Î²-hydroxybutyrate and its copolymer with Î´-Valerolactone Synthesized by Aluminoxane Catalyst - M. Arcana; B. Tanajaya; B. Anwar; C. L. Radiman; M. A. Sulfikar (Institute for Research and Community Services (LPPM) ITB, 2005)
Poly(R,S)-Î²-hydroxybutyrate (PHB) and its copolymers with Î´-valerolactone were synthesized by ring-opening copolymerization of (R,S)-Î²-butyrolactone (Î²-BL) and Î´-valerolactone (Î´-VL) monomers in the presence of a tetraisobutyldialuminoxane catalyst. The biodegradability of these polymers by using activated sludge was studied in an aerobic medium. The objective of this work was to determine the influence of structure and crystallinity of polymers on their degree of biodegradation and initial degradation rate. It was shown that the degradation rate for bacterial P(R)-HB with 100 % (R) isotactic structure was the highest and the final biodegradation was reached around 94 % after incubation time of 35 days. Whereas the final biodegradation about 88 % was obtained for atactic P(R,S)-Î²-HB synthesized by using aluminoxane catalyst. The influence of the structure and crystallinity on the initial biodegradation rate were observed for the copolymers in various composition of comonomers. All these copolymers with the PHB ratio more than 10 % exhibit highly degree of biodegradation, about 85 % after 35 days of incubation time.